Pengukuran Jarak Berbasiskan Stereo Vision - Kartowisastro, Iman Herwidiana (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Measuring distance from an object can be conducted in a variety of ways, including by making use of distance measuring sensors such as ultrasonic sensors, or using the approach based vision system. This last mode has advantages in terms of flexibility, namely a monitored object has relatively no restrictions characteristic of the materials used at the same time it also has its own difficulties associated with object orientation and state of the room where the object is located. To overcome this problem, so this study examines the possibility of using stereo vision to measure the distance to an object. The system was developed starting from image extraction, information extraction characteristics of the objects contained in the image and visual distance measurement process with 2 separate cameras placed in a distance of 70 cm. The measurement object can be in the range of 50 cm - 130 cm with a percentage error of 5:53%. Lighting conditions (homogeneity and intensity) has a great influence on the accuracy of the measurement results.